Inflation targets and intervals – an overview of the issues - Mikael Apel; Carl Andreas Claussen (Sveriges Riksbank Economic Review, 2017)
In this article, we analyse the advantages and disadvantages of different ways of formulating inflation targets that involve an interval. We first review the international debate of ten to fifteen years ago on how an inflation target should best be designed. We then discuss the arguments in the current Swedish debate in light of this. One central conclusion is that if the inflation target is credible, monetary policy can be flexible and consider factors other than inflation – such as output and employment – even without an interval. A `tolerance band' can open for more flexibility if it increases the credibility of the inflation target, but it could also reduce flexibility if it creates more inflation uncertainty or if ending up outside the interval is very costly. A `target range' entails a major change to the monetary policy framework. It would allow the central bank to aim at different levels for inflation at different times. But as inflation expectations may become less firmly anchored, economic fluctuations may become greater.
Keywords: E52; E58; 330; Monetary policy; inflation target; interval